2016
DOI: 10.1186/s12931-016-0463-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of TROP2 in airway basal cells potentially contributes to airway remodeling in chronic obstructive pulmonary disease

Abstract: BackgroundThe airway epithelium of chronic obstructive pulmonary disease (COPD) patients undergoes aberrant repair and remodeling after repetitive injury following exposure to environmental factors. Abnormal airway regeneration observed in COPD is thought to originate in the stem/progenitor cells of the airway epithelium, the basal cells (BCs). However, the molecular mechanisms underlying these changes remain unknown. Here, trophoblast cell surface antigen 2 (TROP2), a protein implicated in the regulation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Here, we showed that airway epithelial thickness, total epithelial cell count, Ki67+ epithelial cells were positively correlated with airway epithelial-specific PTCH1 protein expression in airway epithelial tissue in all subjects. Consistent with our finding, Liu and colleagues showed a progressive and significant increase in proliferation index (Ki67+ cell) in the airway epithelium of patients without and with COPD (moderate severity), respectively 48 . Our data further demonstrated that severe COPD patients have reduced Ki67+ cells in the airway epithelium compared to moderate COPD patients, which is suggestive of cellular exhaustion.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we showed that airway epithelial thickness, total epithelial cell count, Ki67+ epithelial cells were positively correlated with airway epithelial-specific PTCH1 protein expression in airway epithelial tissue in all subjects. Consistent with our finding, Liu and colleagues showed a progressive and significant increase in proliferation index (Ki67+ cell) in the airway epithelium of patients without and with COPD (moderate severity), respectively 48 . Our data further demonstrated that severe COPD patients have reduced Ki67+ cells in the airway epithelium compared to moderate COPD patients, which is suggestive of cellular exhaustion.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been reported that increased expression of TROP-2 in airway basal cells could contribute to proliferation of such cells derived from smokers with chronic obstructive pulmonary disease (COPD) [ 77 ]. TROP-2 basal cells exhibit improved proliferation with activation of the ERK1/2 phosphorylation signaling pathway, and with an EMT-like change, not unlike the effects found in oncology.…”
Section: Trop-2 In Stem Cell Biology and Other Diseasesmentioning
confidence: 99%
“…In patients with chronic obstructive pulmonary disease (COPD), Trop2 expression is significantly increased in airway basal cells, acting as the stem/progenitor cells of airway epithelium [ 32 ]. In vitro, Trop2 promotes proliferation and self-renewal of basal cells and induces an EMT-like phenotype and the release of proinflammatory cytokines.…”
Section: Trop2 In Healthy Tissue and Developmentmentioning
confidence: 99%